The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1785/0120130300
|View full text |Cite
|
Sign up to set email alerts
|

Some Thoughts on Declustering in Probabilistic Seismic-Hazard Analysis

Abstract: In this paper, we discuss in depth, one of the basic procedures that stands behind probabilistic seismic-hazard analysis (PSHA), that is, the declustering of the seismicity rates. First, we explore the technical, scientific, and practical motivations that led to introducing the declustering of seismicity rates. Then, we show that for PSHA, declustering is essential only to minimize a spatial distortion of the earthquake occurrence process, but, conversely, it may lead to significant underestimation of the true… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 18 publications
1
63
0
Order By: Relevance
“…The importance of aftershocks in seismic hazard has been highlighted previously. For instance, Marzocchi and Taroni (2014) concluded that aftershocks should be included in probabilistic seismic hazard analysis (PSHA), because only using the PSHA result from the declustered catalog underestimated hazard rates. Approaches for including aftershocks can be distinguished by the treatment of mainshocks: (1) long-term (years to centuries), timeindependent approaches that integrate aftershock hazard on unconditional mainshock occurrence; (2) short-term (days to years) approaches that estimate aftershock hazard conditional on a specified mainshock source.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of aftershocks in seismic hazard has been highlighted previously. For instance, Marzocchi and Taroni (2014) concluded that aftershocks should be included in probabilistic seismic hazard analysis (PSHA), because only using the PSHA result from the declustered catalog underestimated hazard rates. Approaches for including aftershocks can be distinguished by the treatment of mainshocks: (1) long-term (years to centuries), timeindependent approaches that integrate aftershock hazard on unconditional mainshock occurrence; (2) short-term (days to years) approaches that estimate aftershock hazard conditional on a specified mainshock source.…”
Section: Introductionmentioning
confidence: 99%
“…that an immigrant event is equally likely to occur at each point in time, and that the time between each pair of immigrant events (known as the 'inter-arrival times') follows a time-independent Exponential(μ) distribution. However, this conflicts with findings elsewhere in the seismology literature, where there is substantial doubt over whether the occurrence times of mainshock earthquakes is really Poissonian (Tahernia et al 2014;Ordaz and Arroyo 2016;Marzocchi and Taroni 2014). Although ETAS immigrant events are not strictly equivalent to mainshocks as defined elsewhere in the seismology literature (since there is no requirement that an ETAS immigrant should have larger magnitude than its offspring), this still seems to cast some doubt on the Poissonian assumption.…”
Section: Introductionmentioning
confidence: 76%
“…In this appraisal, the fact that earthquakes follow a Poisson distribution in time has been considered to minimize any spatial bias of the earthquake occurrence process, as it usually is in most seismic-hazard assessments, both in zoning and nonzoning methods. Some recent papers (e.g., Boyd, 2012;Marzocchi and Taroni, 2014) advise the use of aftershocks in the seismic-hazard computation, noticing the underestimation of the seismic hazard when the declustering process is carried out, and proposing different initial approaches to correct it. Taking into account the characteristics of the catalog used in this work, especially its spatial completeness, as well as the different behavior of observed seismic sequences, among other issues, we were ultimately led to follow a typical zoning method.…”
Section: Methodsmentioning
confidence: 99%